HUBUNGAN LITERASI EKONOMI DENGAN PEMAHAMAN STRUKTUR EKONOMI NASIONAL PESERTA DIDIK SEKOLAH DASAR - Opermadia, Suci; Irawanis, Susi; Surya Elita, Ade; Arios; Sumanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between economic literacy and the understanding of national economic structure among fourth-grade elementary school students at SDN 191/III Koto Cayo. The importance of economic literacy at the elementary school level is increasingly recognized as a foundation for building students' understanding of broader economic concepts, including the national economic structure. Despite its significance, research on economic literacy among elementary school students in rural areas remains limited. This study employed a quantitative correlational method involving 30 fourth-grade students as the research population and sample. Data were collected through instruments measuring economic literacy and understanding of national economic structure, both of which had been validated and declared reliable. The data were analyzed using Pearson Product Moment correlation. The results showed that the correlation coefficient (r) between economic literacy and understanding of national economic structure was 0.724, which is significant at p < 0.05. The coefficient of determination (r²) was 0.524, indicating that economic literacy explained 52.4% of the variance in students' understanding of national economic structure. These findings suggest a strong and statistically significant positive relationship between the two variables. The study concludes that improving economic literacy programs in elementary schools, especially in rural areas, is essential for enhancing students' comprehension of national economic concepts. Recommendations are provided for teachers, school administrators, and policymakers to integrate economic literacy content more systematically into the elementary school curriculum.